2023
DOI: 10.1002/lary.31083
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation and Validation of the Laryngoscore and the mini‐Laryngoscore

Camille Clarysse,
Jeroen Meulemans,
Charlotte van Lierde
et al.

Abstract: ObjectiveThe Laryngoscore was described in 2014 as a practical preoperative assessment tool to predict difficult laryngeal exposure (DLE) during transoral approaches to the larynx. In 2019 the authors proposed a version with a reduced number of variables, called the mini‐Laryngoscore. We aim to critically appraise and externally validate these two tools and if needed and possible, to optimize these tools.Methods103 consecutive patients who underwent a microlaryngoscopy between November 2017 and June 2020 at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The absence of teeth increases the mouth space and enlarges the IIG. Some researchers have observed that the likelihood of DLE increases progressively by dental status, in the order of edentulous, partially edentulous, normal teeth, and prominent teeth [ 4 , 39 , 40 ]. Considering the various anatomical distances, even a minor difference in each one-dimensional parameter can combine to yield a significant discrepancy in the three-dimensional structure of the pharyngeal space.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of teeth increases the mouth space and enlarges the IIG. Some researchers have observed that the likelihood of DLE increases progressively by dental status, in the order of edentulous, partially edentulous, normal teeth, and prominent teeth [ 4 , 39 , 40 ]. Considering the various anatomical distances, even a minor difference in each one-dimensional parameter can combine to yield a significant discrepancy in the three-dimensional structure of the pharyngeal space.…”
Section: Discussionmentioning
confidence: 99%